Bipolar localization of Bacillus subtilis topoisomerase IV, an enzyme required for chromosome segregation - Huang, Wai Mun (The National Academy of Sciences, 1998)
In Bacillus subtilis, parE and parC were shown to be essential genes for the segregation of replicated chromosomes. Disruption of either one of these genes resulted in failure of the nucleoid to segregate. Purified ParE and ParC proteins reconstituted to form topoisomerase IV (topo IV), which was highly proficient for ATP-dependent superhelical DNA relaxation and decatenation of interlocked DNA networks. By immunofluorescence microscopy and by directly visualizing fluorescence by using green fluorescence protein fusions, we determined that ParC is localized at the poles of the bacteria in rapidly growing cultures. The bipolar localization of ParC required functional ParE, suggesting that topo IV activity is required for the localization. ParE was found to be distributed uniformly throughout the cell. On the other hand, fluorescence microscopy showed that the GyrA and GyrB subunits of gyrase were associated with the nucleoid. Our results provide a physiologic distinction between DNA gyrase and topo IV. The subcellular localization of topo IV provides physical evidence that it may be part of the bacterial segregation machinery.